Sustaining Excellence, UMP is now known as UMPSA - Mimi Rabita, Abdul Wahit (UMPSA, 2023)
PEKAN, 30 July 2023 - After 21 years of glory, Universiti Malaysia Pahang (UMP) is now branded as Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA).